PENGARUH CITRA DAN KEPERCAYAAN MEREK TERHADAP LOYALITAS MEREK: SURVEI PELANGGAN LUX CAIR DI CARREFOUR MT. HARYONO - Mohamad Rizan (Jurnal Ilmiah Econosains, 2011)
Abstract Generally, the purposes of this research are: (1) Knowing the description of the brand image, brand trust, and brand loyalty, (2) Determining/Knowing the influence of brand image towards brand loyalty, (3) Determining/Knowing the influence of brand trust towards brand loyalty, (4) Determining/Knowing the influence of brand image and brand trust simultaneously towards brand loyalty. The units of analysis are buyers or users of Lux at Carrefour MT. Haryono. Observation units are 200 respondents who are the visitors of Carrefour MT. Haryono, who have bought or used liquid Lux for one year or more. The research type is descriptive and research method using explanatory causal survey. Descriptive analysis showed: (a) benefit dimension is the most dominant dimension in brand image variables, (b) company characteristic dimension is the most dominant dimension in brand trust variables, and (c) commitment dimension is the most dominant dimension in brand loyalty variables. The results of hypothesis testing are: 1) brand image variable has a significant influence to brand loyalty with beta coefficient of 0.297, T-test of 4.850 with significance level of 0.000; 2) brand trust variable has a significant influence to brand loyalty with beta coefficient of 0.468, T-test of 7.657 with significance level of 0.000; 3) the influence of brand image and brand trust simultaneously towards brand loyalty is 44.5%. Keywords: Brand Image, Brand Trust, Brand Loyalty, Lux